+0  
 
0
92
5
avatar+4690 

Help 9

 Dec 7, 2018
 #1
avatar+580 
-1

Our x2 and x1 is 4 and -5, respectively.

Similarly, our y2 and y1 is -9 and 2, respectively. Now plug them in:

\(d=\sqrt{[4-(-5)]^2+[-9-2]^2}\)

Can you solve that?

 

You are very welcome!

:P

 Dec 7, 2018
 #2
avatar+4690 
0

can you elvaluate that a bit more

NotSoSmart  Dec 7, 2018
 #3
avatar+98102 
+1

[  ( 4 - (-5)]^2  =  [ 4 + 5]^2  = 9^2  =  81     (1)

 

[ ( -9 - 2 ]^2  = [ -11]^2 = 121    (2)

 

Add (1) and (2), NSS

 

Take the square root of this sum and that will be your answer

 

cool cool cool

CPhill  Dec 7, 2018
 #4
avatar+4690 
+1

It's C?

NotSoSmart  Dec 9, 2018
 #5
avatar+98102 
0

Correct!!!!

 

 

cool cool cool

CPhill  Dec 9, 2018

32 Online Users

avatar
avatar
avatar
avatar